Comparison of monophasic and biphasic hyaluronic acid fillers: a meta-analysis across facial regions in Asian populations - Ingyu Lee; JinHan Lee; SeoWon Kang; Hyungin Cho; Ki Won Lee; Dongkeun Lim (Journal of Cosmetic Medicine)
Hyaluronic acid (HA) fillers are widely used in nonsurgical facial rejuvenation to restore volume and enhance contour. Monophasic and biphasic fillers are commonly used; however, there is limited consensus regarding their optimal application in different facial regions, particularly in Asian populations with unique anatomical and aesthetic preferences. This meta-analysis evaluated the efficacy and safety of monophasic and biphasic HA fillers, focusing on key facial areas, including the nasolabial folds, cheeks, and nose, in Asian populations. A systematic literature search of the PubMed, KoreaMed, DBpia, Google Scholar, Embase, and Cochrane Library databases was performed to identify relevant studies published between 2014 and 2023. After screening 416 records and assessing the full texts, 17 studies comprising 1,765 patients were included. Data regarding patient satisfaction, adverse effects, and HA-filler performance were extracted and analyzed using a random effects model. Standardized mean difference (SMD) with corresponding 95% confidence interval were calculated. Monophasic fillers demonstrated superior integration in dynamic areas, such as the nasolabial folds, with fewer side effects such as swelling and bruising. Biphasic fillers demonstrated greater volume retention and structural support for deeper applications, such as nose reshaping and cheek augmentation, but had higher rates of transient adverse effects. The SMD values ranged from 0.60 to 0.70, with minimal publication bias. Monophasic fillers excelled in the dynamic regions, whereas biphasic fillers were more optimal for deeper structural supports. Combining both filler types may optimize outcomes. Further research investigating long-term efficacy and safety is warranted.